2015
DOI: 10.1002/mus.24745
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive nerve stimulation and single‐fiber electromyography in the evaluation of patients with suspected myasthenia gravis or Lambert–Eaton myasthenic syndrome: Review of recent literature

Abstract: Electrodiagnostic testing continues to be useful for diagnosis of MG and LEMS, although the quality of the evidence is not great. This literature review summarizes RNS and jitter measurement of facial and respiratory muscles and use of concentric needle EMG for SFEMG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 71 publications
(83 reference statements)
1
28
0
2
Order By: Relevance
“…Pathological conditions such as dystrophy (Lacourpaille et al, 2017 ) or spasticity (Granata et al, 2000 ) influence the EMD. Therefore, it is critical to detect changes in EMD due to muscle diseases such as myasthenia gravis or Lambert-Eaton myasthenic syndrome where the electromechanical coupling is disrupted (Chiou-Tan and Gilchrist, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pathological conditions such as dystrophy (Lacourpaille et al, 2017 ) or spasticity (Granata et al, 2000 ) influence the EMD. Therefore, it is critical to detect changes in EMD due to muscle diseases such as myasthenia gravis or Lambert-Eaton myasthenic syndrome where the electromechanical coupling is disrupted (Chiou-Tan and Gilchrist, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…This was unexpected because earlier reports demonstrated increases in CMAP amplitude after DAP administration . Several factors may have played a role in these inconsistent results, among them the small number of participants, particularly at the end of withdrawal, due to rescue, and differences in the CMAP technique used at the different study sites . Indeed, CMAPs from only 10 of 12 (83%) of participants who continued DAP met the predetermined criteria for acceptability (see Table S3 online) on the first day of withdrawal (study day 3) and the number of acceptable CMAP studies was lower at each subsequent assessment.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,14,25 Several factors may have played a role in these inconsistent results, among them the small number of participants, particularly at the end of withdrawal, due to rescue, and differences in the CMAP technique used at the different study sites. [26][27][28] Indeed, CMAPs from only 10 of 12 (83%) of participants who continued DAP met the predetermined criteria for acceptability (see Table S3 online) on the first day of withdrawal (study day 3) and the number of acceptable CMAP studies was lower at each subsequent assessment. This pattern was also observed in the group withdrawn from DAP: only 14 of 18 (78%) participants had acceptable CMAP studies on study day 3, and the number of acceptable CMAP studies declined at each subsequent assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies demonstrated that long grafts resulted in poor axonal regeneration and functional recovery compared with short grafts concurrent with an accumulation of cellular senescence. 3 As tissue subjected to prolonged ischemia develops numerous pathological processes, including cell damage, [4][5][6][7][8][9][10][11] an explanation for the poor regenerative outcomes and/or accumulation of senescence could be due to poor vascularization leading to ischemia and pathological consequences in long nerve grafts and constructs.…”
Section: Discussionmentioning
confidence: 99%